A unique case of extra-cerebral diffuse glioneuronal tumor with oligodendroglioma-like features and nuclear clusters - Wu Maurice, MD; Naderian Ashkun, MD; Iyengar Krishnan, MBBS, MD, DNB, FRCPA; Coulthard Alan, FRCSEd, FRCR, FRANZCR, GAICD; Jeffree Rosalind, MBBS, MSc, FRACS, MHE (Radiology Case Reports)
Diffuse glioneuronal tumor with oligodendroglioma-like features and nuclear clusters (DGONC) is a newly recognized provisional entity in the fifth edition of the WHO Classification of Central Nervous System Tumors, typically found in pediatric patients with supratentorial disease. We describe a male in his forties who presented with recurrent seizures and was found to have a heavily calcified lesion in the left temporal lobe and an additional lesion in the sacral region of the thecal sac; tissue biopsy of the sacral lesion demonstrated an oligodendroglioma-like morphology, strong synaptophysin and OLIG2 expression, and absent widespread GFAP staining, consistent with DGONC. This represents an unusual occurrence of DGONC outside the supratentorial region, with imaging findings that mimicked a chronic inflammatory process. Radiologists should be aware of the potential for DGONC to present in atypical locations and should consider it in the differential diagnosis of apparently non-neoplastic lesions.